Differentiating tic electrophysiology from voluntary movement in the human thalamocortical circuit. Issue 5 (5th March 2020) - Cagle, Jackson N; Okun, Michael S; Opri, Enrico; Cernera, Stephanie; Molina, Rene; Foote, Kelly D; Gunduz, Aysegul
Abstract : Objectives: Tourette syndrome is a neurodevelopmental disorder commonly associated with involuntary movements, or tics. We currently lack an ideal animal model for Tourette syndrome. In humans, clinical manifestation of tics cannot be captured via functional imaging due to motion artefacts and limited temporal resolution, and electrophysiological studies have been limited to the intraoperative environment. The goal of this study was to identify electrophysiological signals in the centromedian (CM) thalamic nucleus and primary motor (M1) cortex that differentiate tics from voluntary movements. Methods: The data were collected as part of a larger National Institutes of Health-sponsored clinical trial. Four participants (two males, two females) underwent monthly clinical visits for collection of physiology for a total of 6 months. Participants were implanted with bilateral CM thalamic macroelectrodes and M1 subdural electrodes that were connected to two neurostimulators, both with sensing capabilities. MRI scans were performed preoperatively and CT scans postoperatively for localisation of electrodes. Electrophysiological recordings were collected at each visit from both the cortical and subcortical implants. Results: Recordings collected from the CM thalamic nucleus revealed a low-frequency power (3–10 Hz) increase that was time-locked to the onset of involuntary tics but was not present during voluntary movements. Cortical recordings revealed beta power decrease in M1 that was present during tics and voluntary movements. Conclusion: We conclude that a human physiological signal was detected from the CM thalamus that differentiated tic from voluntary movement, and this physiological feature could potentially guide the development of neuromodulation therapies for Tourette syndrome that could use a closed-loop-based approach.